Enterococcus hirae Mitral Valve Infectious Endocarditis: A Case Report and Review of the Literature - Roberta Gaudiano; Marcello Trizzino; Salvatore Torre; Roberta Virruso; Fabio Fiorino; Vincenzo Argano; Antonio Cascio (MDPI AG, 2023)
Enterococcus hirae is a rare pathogen in human infections, although its incidence may be underestimated due to its difficult isolation. We describe the first known case of E. hirae infective endocarditis (IE), which involves the mitral valve alone, and the seventh E. hirae IE worldwide. Case presentation: a 62-year-old male was admitted to our department with a five-month history of intermittent fever without responding to antibiotic treatment. His medical history included mitral valve prolapse, recent pleurisy, and lumbar epidural steroid injections due to lumbar degenerative disc disease. Pre-admission transesophageal echocardiography (TEE) showed mitral valve vegetation, and Enterococcus faecium was isolated on blood cultures by MALDI-TOF VITEK MS. During hospitalization, intravenous (IV) therapy with ampicillin and ceftriaxone was initiated, and E. hirae was identified by MALDI-TOF Bruker Biotyper on three blood culture sets. A second TEE revealed mitral valve regurgitation, which worsened due to infection progression. The patient underwent mitral valve replacement with a bioprosthetic valve and had an uncomplicated postoperative course; he was discharged after six weeks of IV ampicillin and ceftriaxone treatment.